국내외 호흡기 및 인체 마이크로바이옴 연구 - 최성미; 조상헌; 이하나 (Allergy asthma & respiratory disease, 2016)
During the second half of the 2000s, the significant impact of human microbiome on human diseases and health conditions was found. Since the Human Microbiome Project, many microbiome studies have been reported in domestic and international references. Gastrointestinal tract microbiome has been most investigated so far, and the association with illness has been demonstrated in many diseases. Recently, the range of study was extended to multiple human organs, such as the respiratory tract, skin, and urogenital tract. Given the scale and speed of research and development in recent years, the role of microbiome in many diseases would be established before long. In this review, we aimed to summarize the current status of microbiome studies in Korea and foreign countries with an emphasis on respiratory tract microbiome. The main concept and analytical methods for microbiome research, associations of microbiome and diseases, and research projects on Korean microbiome are reviewed. KCI Citation Count: 2